PHENOGENETIC ASPECTS OF DERMATOGLYPHIC CHANGES AT ATOPIC DERMATITIS - Cherkasov, V.G.; Gunas, I.V.; Gara, A.V. (World of Medicine and Biology, 2015)
Aim of our work - set features of dermatoglyphics indicators of girls from Podillia, with atopic dermatitis (AD) of mild to moderate severity. Materials and methods Were examined 42 girls aged from 12 to 17 years, patients with atopic dermatitis who were on outpatient observation of children’s hospitals Podilsky region of Ukraine. In the role of a control group from database of Scientific and Research Center Vinnitsa National Medical University named after Pirogov were taken dermatoglyphic indicators of 167 practically healthy patients of similar age girls, also in the third generation residents of Podilla. Verify the diagnosis of AD was performed according to the diagnostic criteria J.M. Hanifin and G. Rajka (1980). Using coefficient SCORAD (k), which is calculated by the appropriate formulas objectively assessed the degree of severity of skin process in each surveyed child: k < 20 - mild, 20 < k < 40 - average degree, k > 40 - severe degree. Found that in 33 patients experienced girls light, in 11 - medium, severe disease among surveyed were not found. Dermatoglyphic study conducted by using the conventional method of H. Cummins and Ch. Midlo (1961). Statistical analysis of the results conducted in the package "STATISTICA 5.5". Results. Discussions As a result of the study revealed clinical polymorphism association of atopic dermatitis skin of patients with papillary peculiarities in patient’s girls. Easy severity of AD in patients girls correlates with the presence of random patterns on the fingers I, arches on II and on V fingers, arches and random patterns on fingers IV and accompanied by low frequency ulnar loops on IV and V fingers of both hands; low value delta index of right, left and both hands, high values of atd angles of right and left palms, ctd, atb of left palm, length of the segment a-d of right and left hands, comb account a-b of both palms, b-c of right palm, and presence of an intermediate, central axis of threeradii and combinations of threeradii on both hands and presence of patterns on hypothenar, in I, II interdigital spaces of right palm and IV - of both palms. The course of atopic dermatitis of moderate severity in patients girls associated with the presence of central pockets on the finger I of the right and left hands, arches – on the second finger of the right and left hands, central pocket on the third finger of the left hand, arcs - the IV and V fingers of the left hand; with comb row on the II fingers of the left hand and right hand index delta and low values of 10 fingers; the presence of ctd angles of both hands, dat of right palm with high values, the presence of central three radius central axis and combinations of threeradiuses on both palms and patterns on of both palms thenar, hypothenar and interdigital interval I of right hand. Differences of dermatoglyphics in girls suffering from AD moderate severity compared with such of mild severity found only for quality signs finger dermatoglyphics and apparent: greater frequency of central pockets on the I fingers of the right and on the fourth finger of the left hand, and ulnar loops on the fourth finger of right hand.